Pengaruh Political Connection dan Local Corruption terhadap Corporate Cash Holding di Indonesia - Devi Widyaningrum; Dwi Marlina Wijayanti (Universitas Warmadewa, 2022)
This study aims to determine the effect of political connection and local corruption on cash holding companies in Indonesia. The research that has been done on this topic has not been consistent with the results, so that this topic still needs to be done for research. To resolve the inconsistency of the results of previous research, this study will use a sample that focuses on companies listed in the LQ-45 index. This study is included in quantitative research. The sample used in this study are companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2020. Based on the multiple regression analysis that has been carried out, it can be concluded that political connection do not have a significant influence on cash holdings. Meanwhile, local corruption has a negatif effect on the company's cash holding